Modulation of Intrinsic Brain Connectivity by Implicit Electroencephalographic Neurofeedback - Dobrushina, Olga R.; Vlasova, Roza M.; Rumshiskaya, Alena D.; Litvinova, Liudmila D.; Mershina, Elena A.; Sinitsyn, Valentin E.; Pechenkova, Ekaterina V. (Frontiers in Human Neuroscience, 2020)
Despite the increasing popularity of neurofeedback, its mechanisms of action are still poorly understood. This study aims to describe the processes underlying implicit electroencephalographic neurofeedback. Fifty-two healthy volunteers were randomly assigned to a single session of infra-low frequency neurofeedback or sham neurofeedback with electrodes over the right middle temporal gyrus and the right inferior parietal lobule. They observed a moving rocket, the speed of which was modulated by the waveform derived from a band-limited infra-low frequency filter. Immediately before and after the session the participants underwent a resting state fMRI. Network-based statistical analysis was applied, comparing post- vs. pre-session and real vs. sham neurofeedback conditions. As a result, two phenomena were observed. First, we described a brain circuit related to the implicit neurofeedback process itself, consisting of the lateral occipital cortex, right dorsolateral prefrontal cortex, right ventral and bilateral dorsal striatum. Second, we found increased connectivity between key regions of the salience, language and visual networks, which is indicative of integration in sensory processing. Thus, it appears that a single session of implicit infra-low frequency electroencephalographic neurofeedback leads to significant changes in intrinsic brain connectivity.